2022
DOI: 10.2337/dc22-0110
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights Into the Heterogeneity of Glucose Response Classes in Youths With Obesity: A Latent Class Trajectory Approach

Abstract: OBJECTIVE In a large, multiethnic cohort of youths with obesity, we analyzed pathophysiological and genetic mechanisms underlying variations in plasma glucose responses to a 180 min oral glucose tolerance test (OGTT). RESEARCH DESIGN AND METHODS Latent class trajectory analysis was used to identify various glucose response profiles to a nine-point OGTT in 2,378 participants in the Yale Pathogenesis of Youth-Onset T2D study, o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…In our study, the cell size distribution profile of abdominal SAT biopsies revealed fewer but larger adipocytes in participants classified as hypersecretors, in whom adipose hypertrophy prevails over hyperplasia. Furthermore, a larger adipocyte size at baseline was associated with short-term increases in β-cell glucose sensitivity, possibly perpetuating chronic hyperinsulinemia, which is noteworthy in a population where β-cell function generally deteriorates over time ( 12 , 59 ). These observations align with the current knowledge that hypertrophic adipocytes are less susceptible to insulin antilipolytic action and may provide a chronic FFA overload to the β-cell ( 28 ) to enhance insulin secretion ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 98%
“…In our study, the cell size distribution profile of abdominal SAT biopsies revealed fewer but larger adipocytes in participants classified as hypersecretors, in whom adipose hypertrophy prevails over hyperplasia. Furthermore, a larger adipocyte size at baseline was associated with short-term increases in β-cell glucose sensitivity, possibly perpetuating chronic hyperinsulinemia, which is noteworthy in a population where β-cell function generally deteriorates over time ( 12 , 59 ). These observations align with the current knowledge that hypertrophic adipocytes are less susceptible to insulin antilipolytic action and may provide a chronic FFA overload to the β-cell ( 28 ) to enhance insulin secretion ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 98%
“…More than one-third of U.S. adolescents with obesity have a prediabetes glycemic profile (9,10), with ~35% progressing to persistent dysglycemia or overt diabetes during adulthood (11). Unlike the gradual prolonged metabolic changes preceding adult-onset type 2 diabetes (T2D), a rapid progression of dysglycemia and β cell failure in the context of insulin resistance occurs in youth-onset T2D (12)(13)(14)(15) with at least 1 diabetes complication occurring before the age of 30 years (16). Neverthless, there are no approved drugs to treat prediabetes in youths with a temporally limited window of intervention to prevent diabetes complications after the disease onset.…”
Section: Introductionmentioning
confidence: 99%
“…Sonia Caprio began a set of talks on the progression from childhood risks to diseases in adults, describing her studies of the four classes of obese youth with progressively worsening glucose tolerance, in association with hyperinsulinemia, decreased insulin sensitivity, decreased insulin clearance, and increased liver fat. 21 Petter Bjornstad reviewed an analysis of 517 persons with youth‐onset type 2 diabetes followed from 2011, at mean age 14, for an average 7.5 years, with HbA1c increasing from 6.0% to 9.3%; both hyperfiltration and insulin resistance tracked with development of microalbuminuria in 55% of the group, with an additional 17% developing hyperfiltration (estimated glomerular filtration rate ≥ 135). 22 A study of 161 Pima Indians with type 2 diabetes who underwent renal biopsy showed that, compared with adult‐onset, youth‐onset diabetes was associated with greater levels of albuminuria and with greater glomerular basement membrane width and mesangial fractional volume independent of historic A1c control, age, and duration, with the youth‐onset group having greater risk of progression to kidney failure.…”
mentioning
confidence: 99%
“…Sonia Caprio began a set of talks on the progression from childhood risks to diseases in adults, describing her studies of the four classes of obese youth with progressively worsening glucose tolerance, in association with hyperinsulinemia, decreased insulin sensitivity, decreased insulin clearance, and increased liver fat 21 . Petter Bjornstad reviewed an analysis of 517 persons with youth‐onset type 2 diabetes followed from 2011, at mean age 14, for an average 7.5 years, with HbA1c increasing from 6.0% to 9.3%; both hyperfiltration and insulin resistance tracked with development of microalbuminuria in 55% of the group, with an additional 17% developing hyperfiltration (estimated glomerular filtration rate ≥ 135) 22 .…”
mentioning
confidence: 99%